Sedimentary evolution of the marine Agua de la Mula Member (Agrio Formation, Lower Cretaceous) in the central Neuquén Basin: Source areas and paleogeographic considerations from a distal setting. (December 2019) - Comerio, Marcos; Fernández, Diana Elizabeth; Gutiérrez, Carolina; Ballivián Justiniano, Carlos; González Estebenet, María Candela; Pazos, Pablo José
Abstract: The Agua de la Mula Member (Upper Hauterivian–Lower Barremian) of the Agrio Formation represents the infill of a mixed siliciclastic–carbonate low-gradient ramp system comprising both hydrocarbon sand reservoirs and a source rock interval considered as potential unconventional shale play. The present study analyzes the unit in offshore settings (Loma La Torre section) where high-quality, laterally continuous exposures allowed the recognition of muddy subaqueous clinoforms prograding northwestward. The muddy-dominated facies throughout the entire section represent an overall evolution from distal outer-ramp to inner-ramp settings associated with tidal flat deposits. Based on previous sedimentological studies and paleogeographic reconstruction, four facies belts are refined for the unit in the central Neuquén Basin: (1) shallow marine and deltaic facies to fluvial deposits documented in the subsurface (mainly siliciclastic); (2) mid-ramp to inner-ramp with subordinated outer-ramp settings (mainly siliciclastic); (3) outer-ramp to distal mid-ramp settings with muddy subaqueous clinoforms (mixed siliciclastic–carbonate); and, (4) basinal to outer-ramp areas (carbonate-dominated). In addition to the main sediment input from the south and southeastern margin of the basin, sedimentological and stratigraphic approaches suggest a sediment supply from the eastern and northeastern regions. Sporadic ash-fall deposits also indicate that the coetaneous magmatic arc was active. In fact, LA-ICP-MS U–Pb zircon ages from two tuff layers recorded in the study section yield an age interval of less than 1 m.yr., which allowed us to estimate the sedimentation and progradation rates of a clinoform set. Finally, four asymmetrical sequences are recognized comprising thin (carbonate–siliciclastic) transgressive systems tracts and thick regressive (highstand) systems tracts with stacked parasequences of shallowing-upward siliciclastic-dominated facies. These sequences are correlated with the four (4th-order) sequences previously defined in proximal settings. The observations suggest that sea-level changes were relatively synchronous events and, according to the present knowledge, controlled not only by orbital mechanisms but also by tectonism. Highlights: Muddy subaqueous clinoforms in outer-ramp to distal mid-ramp settings. Sedimentation and progradation rates of a clinoform set. High frequency (4th-order) sequences. Paleogeography, principal and secondary source areas.